Serum Levels of Fetuin A and 8-hydroxydeoxyguanosine in Morbidly Obese Subjects - Himmetoglu, S.; Teksoz, S.; Zengin, K.; Yesim, T.; Taskın, M.; Dincer, Y. (Experimental and Clinical Endocrinology & Diabetes, 2013)
Insulin resistance is one of the feature of obesity. Fetuin A is inhibitor of insulin receptor which belongs the family of receptor tyrosine kinase. It has been observed that fetuin-null mice are resistant to diet-induced obesity and they exhibit increased insulin sensitivity. Increased production of reactive oxygen species is suggested to be associated with insulin resistance. Attacks of reactive oxygen species to DNA results in base oxidation. Among the oxidized bases, 8-hydroxydeoxyguanosine is predominant lesion with pro-mutagenic potential. In the present study; measurement of serum levels of fetuin A and 8-hydroxydeoxyguanosine in obese subjects (n=46) and healthy controls (n=22), and examination of the relations between these parameters and insulin resistance have been purposed. Blood samples were taken form morbidly obese subjects after a 12 h fasting. Serum levels of fetuin A and 8-hydroxydeoxyguanosine were measured by ELISA. Statistical analysis was performed by Mann Whitney U test and correlations were examined by Spearman correlation coefficient. Serum levels of total cholesterol, HDL, LDL, VLDL, triglycerides, free T3, free T4, fasting glucose, c-peptide and %HbA1c in the obese group were found to be different from those in the control group. Serum level of fetuin A was found to be higher, 8-hydroxydeoxyguanosine level was found to be lower in the morbid obese group than those in the control group. Fetuin A was found to be positively correlated with HOMA-IR (r:0,40, P<0.05) and negatively correlated with 8-hydroxydeoxyguanosine (r:-0,52, P<0.01). No significant association was determined between body mass index and measured parameters. In conclusion, serum level of fetuin A is high in morbidly obese subjects and is negatively associated with 8-hydroxydeoxyguanosine level in peripheral circulation. Fetuin A may be a promising link between insulin resistance and obesity as well its comorbidities.
Keywords: insulin resistance; oxidative stress; oxidative DNA damage; fetuin A; 8-hydroxydeoxyguanosine